Особенности религиозного жaнрa рaмaзaния в кaзaхской литерaтуре (Вестник КазНУ. Серия Востоковедения, 2017)
The article deals with the artistic features of one of the religious genres– ramazaniya. Some information from the books that were published inthe early twentieth century and analyzed the characteristics of the genreramazaniya in the works of Kariboz.